Inventory, Sourcing, and the Effects of Trade Costs: Theory and Empirical Evidence - Chris Muris; Horst Raff; Nicolas Schmitt; Frank Stähler (Center for Economic Studies and ifo Institute (CESifo), 2023)
We develop a dynamic model of inventory investment and trade to examine how firms adjust to changes in international trade costs when facing a risk of stockouts due to demand uncertainty and order lead times for imports. We study two strategies firms may use to avoid stockouts, namely holding inventories of imports, and engaging in dual sourcing. Both strategies are shown to magnify the protective effects of trade costs. Using transaction-level data for a U.S. steel wholesaler experiencing an episode of Section-201 tariffs, we find strong evidence consistent with this magnification effect. Higher tariffs are shown to significantly reduce both the inventory-sales and the import-sales ratios, as the firm adjusts its stockout avoidance strategies.
Keywords: F12; L81; 330; international trade; import tariff; inventory; dual sourcing; stockout avoidance